Creative leadership strategies for primary school principals to promote teachers’ creativity in Guangxi, China - Zhang, Qingling; Siribanpitak, Pruet; Charoenkul, Nuntarat (Kasetsart Journal of Social Sciences, 2018)
The objectives of this research were 1) to analyze the strengths, weaknesses, opportunities and threats to the creative leadership of primary school principals to promote teachers' creativity in Guangxi, China and 2) to develop creative leadership strategies for primary school principals to promote teachers' creativity in Guangxi, China. The study was mixed method research and involved a sample of 106 schools and 636 school principals and teachers. The instruments used in this study were a questionnaire and a strategic evalu- ation form of suitability and feasibility. The data was analyzed by average, standard de- viation and PINmodiﬁed. The results showed the following: 1) the strength was the facilitating creative potential of every teacher; the weaknesses were the forming and facilitating dynamic creative teacher teams and promoting a school culture of innovation respectively. The political and government policy as the opportunity and the economic, socio-cultural and technological aspects were considered as the threats. 2) Three main strategies were developed including (i) to develop the principals' creative leadership in facilitating the team creativity of teachers to foster students' creativity; (ii) to develop principals' creative leadership in promoting an innovation culture that encourages the individual and team creativity of teachers to foster students' creativity; and (iii) to develop the principals' creative leadership in facilitating the individual creativity of every teacher to foster students’ creativity.